Pengaruh Kualitas Pelayanan, Harga, dan Kualitas Produk Terhadap Kepuasan Konsumen Dimsum Bolobox Dinoyo Malang - Kristaliano, Indira; Askandar, Noor Shodiq; Millaningtyas, Restu (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the influence of service quality, price, and product quality on customer satisfaction at Dimsum Bolobox Dinoyo Malang. This study uses a quantitative approach with the Explanatory Research method. The population used in this study is Dimsum Bolobox Dinoyo Malang. The sample consists of 90 respondents selected using the Malhotra formula. Data collection techniques were conducted through the distribution of online and offline questionnaires to consumers. Data analysis was performed using multiple linear regression to test the simultaneous and partial effects of independent variables on the dependent variable. Data processing was conducted using SPSS software version 31. The results of the study indicate that the variables of Service Quality, Price, and Product Quality simultaneously have a significant effect on consumer satisfaction. Partially, each independent variable, namely Service Quality, Price, and Product Quality, has a positive and significant effect on Consumer Satisfaction. Keyword : Service Quality, Price, Product Quality, and Customer Satisfaction